Effect of intravitreal injections on the progression and prognosis of primary open-angle glaucoma - A.B. Movsisyan; N.G. Glazko; A.Yu. Brezhnev; A.V. Kuroyedov (РМЖ "Клиническая офтальмология")
A.B. Movsisyan1,2, N.G. Glazko1, A.Yu. Brezhnev3, A.V. Kuroyedov2,4 1Hospital for War Veterans No. 2, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Kursk State Medical University, Kursk, Russian Federation 4P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation Intravitreal injections (IVI) have revolutionized management strategies for many disorders, e.g., age-related macular degeneration (AMD), diabetic macular edema, retinal vein occlusion, choroidal inflammatory diseases, and pathologic myopia. Over the last two decades, exponential growth in the rate of IVIs has been seen worldwide. Primary therapeutic modalities include the courses of periodic injections to achieve and maintain the desired effect. Studies on the effects and neuroprotective role of vascular endothelial growth factor (VEGF) and agents blocking its action in various organs and tissues on the retina have demonstrated some differences in the outcomes and their interpretation which potentially affect IVI management strategy and treatment efficacy. Understanding the results and ocular changes in response to therapy (particularly in patients with glaucoma) requires special attention. A predicted increase in life expectancy and the number of patients with glaucoma sugge sts that the number of patients with several eye diseases who require IVIs will inevitably increase. In addition, some studies evaluate glaucoma progression after IVIs. Considering a lack of relevant data on long-term adverse effects on IOP level and cup area, and improvement of visual functions, IVIs are regarded as a safe treatment modality in patients with primary open-angle glaucoma (POAG) and ocular comorbidities that require IVIs. Keywords: intravitreal injections, glaucoma, vascular endothelial growth factor, retinal ganglionic cells, retinal nerve fiber layer, intraocular pressure, optical coherence tomography, optic disc. For citation: Movsisyan A.B., Glazko N.G., Brezhnev A.Yu., Kuroyedov A.V. Effect of intravitreal injections on the progression and prognosis of primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2021;21(4):227–234 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-227-234.